The effect of taste and taste perception on satiation/satiety: a review. Issue 4 (20th March 2020) - Li, Ting; Zhao, Mu; Raza, Ali; Guo, Junrui; He, Tianpeng; Zou, Tingting; Song, Huanlu
Abstract : As the prevalence of being overweight and obesity has increased worldwide, there is an increasing concern about satiation/satiety that can be achieved by eating. Abstract : As the prevalence of being overweight and obesity has increased worldwide, there is an increasing concern about satiation/satiety that can be achieved by eating. The ability of an individual to perceive tastes in the mouth is believed to be one of the many factors that influence food intake; the taste may affect appetite regulation and energy intake, playing an important role in promoting satiation/satiety. Satiation/satiety is actually induced by food and may be related to physiological and psychological factors such as several basic tastes, the exposure time of the taste and the cognition of different groups and individuals. This paper reviews the mechanism by which taste regulates satiation/satiety and demonstrates how taste and the taste perception of food prompt the brain to send satiation/satiety signals. Existing problems in taste and satiation/satiety and the prospective application of related research in the food industry are addressed, providing a scientific basis and theoretical guidance for the development and utilization of satiation/satiety from the perspective of taste.